Fiscal Cyclicality and Currency Risk Premia - Jiang, Zhengyang (Review of Financial Studies, 2022)
Abstract I develop a model of real exchange rate determination that attributes a central role to the intertemporal government budget condition, which equates the market value of government debt to the present value of government surpluses. To enforce this equilibrium condition in the presence of nominal rigidities, the real exchange rate has to adjust in response to shocks to government surpluses. The model predicts that fiscal shocks account for real exchange rate movements, and the factor structure in fiscal shocks aligns with the factor structure in currency returns. Both predictions are confirmed in the sample of developed countries.